Acceleration of Rooting Ability and Root Development of Coffee Seedlings (Coffea canephora L.) through a Combination of Dormancy Breaking Techniques and Coffee Types - Yora, Muharama; Ilham, Dewi Jayagma; Rahayu, Sisca Novi Suci; Putri, Zahra Tania (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Plant germplasm plays an important role in maintaining genetic diversity and sustainability of plant cultivation, including coffee. Seed viability testing is a crucial step in ensuring seed quality before being used for planting. The role of coffee germplasm development is carried out to store high-potential coffee varieties, including those with good adaptation and resistance properties. In addition to maintaining coffee germplasm, seed viability testing is also important to ensure effective genetic conservation and maintenance of valuable coffee genetic resources. The purpose of this study was to determine the seed viability of several coffee cultivars with several treatments and to determine the viability and vigor of seeds after a long storage period. The experimental design used was a factorial Randomized Block Design (RAK), with two factors. The first factor is the coffee cultivar (K) consisting of 4 levels, namely: K1 = Tuo coffee, K2 = Ciari coffee, K3 = Manak coffee and K4 = Bengkulu coffee. The second factor is the dormancy breaking method (P) which consists of four levels, namely: (1) breaking the dormancy of several coffee seed varieties by giving growth stimulating hormones, namely GA3 300 ppm f (D1), (2) breaking dormancy chemically with H2SO4 with a concentration of 20% (D2), (3) soaking coffee seeds in warm water at a temperature of 60˚C (D3), (4) soaking seeds in plain water (D0). from this study is that by providing the dormancy breaking method with the soaking method with GA3 at a concentration of 300 ppm in increasing the maximum growth potential of coffee seeds, however, giving different types of coffee treatments and combinations of different types of coffee and dormancy breaking have not shown significantly different results.